2012
DOI: 10.1021/ol300845q
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Rh(I)-Catalyzed Cyclization of Arylboron Compounds onto Ketones

Abstract: Rhodium complexes based upon chiral sulfinamide-alkene, TADDOL-derived phosphoramidite, or diene ligands catalyze cyclizations of arylboron compounds onto ketones, generating a variety of products containing five-, six-, or seven-membered rings with good yields and high enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 55 publications
0
26
0
3
Order By: Relevance
“…As we are active in this eld, 12 and aer considering previous literature work [13][14][15] we set out to study the hitherto unknown Scheme 1 Synthetic route to the isoquinolin-1(2H)-one derivatives obtained in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we are active in this eld, 12 and aer considering previous literature work [13][14][15] we set out to study the hitherto unknown Scheme 1 Synthetic route to the isoquinolin-1(2H)-one derivatives obtained in this work.…”
Section: Resultsmentioning
confidence: 99%
“…12h, 23 As far as we are aware, no reports on the intramolecular addition of metal aryl species to aldehydes have been reported to date. [13][14][15] We started our study with (3a) applying literature conditions 24 with Rh, Pd and Cu catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lam and co-workers successfully realized the Rh-catalyzed intramolecular cyclization of arylboron compounds 92 with S/olefin ligand 68 b to produce a variety of the tetrahydroisoquinolin-4-ols 93 in 70-96 % yields and 80-92 % ee (Scheme 28). [46] Very recently, Du and co-workers found that chiral S/ olefin ligand 70 b was highly efficient in Rh-catalyzed formal [3+2] cycloaddition between racemic butadiene monoxide 94 and imines 95 and 97.…”
Section: Chiral S/olefin Hybrid Ligandsmentioning
confidence: 99%
“…Among the various methods, [3] thec atalytic asymmetric arylations of ketones stand out to be most attractive. Despite the recent advances in asymmetric additions of arylboron reagents to aldehydes, [6] activated ketones, [7] or ketones in an intramolecular fashion, [8] few successful results were reported on asymmetric intermolecular addition of aryl boron reagents to simple ketones. Despite the recent advances in asymmetric additions of arylboron reagents to aldehydes, [6] activated ketones, [7] or ketones in an intramolecular fashion, [8] few successful results were reported on asymmetric intermolecular addition of aryl boron reagents to simple ketones.…”
mentioning
confidence: 99%